Al-‘Aulamah wa-atharuha fi hayat al-muslimin wa-maukifihim minha - Siti Fatimah Bt Seman (Universiti Sains Islam Malaysia, 2014)
Globalization is reunion the world without border. It is a new era of colonization leading by the Western Countries. After the falling of world civilization, then comes a new era that's called a globalization. That's why the whole world dominated totally from all aspects of life like economics, politics, armies, cultures, and religions. Those countries that refuse globalization will grind by this colonizer through pouring or being attacked. Globalization nowadays is appearing only to control the other countries. By the way, if we think deeply we'll be find the whole of world nowadays faced the globalization either by accepted a positive prospective and refused a negative aspect. We as a Muslim, must face the globalization based on our faith. So that we take the benefit from this globalization in order to make our life better.